Framing Islamic History Through Interactive Game (Case Study: Ibn Battuta Games) - Nugrahani, Rahina; Wibawanto, Wandah (KnE Social Sciences, 2017)
Media in various platforms have a significant role in constructing the paradigm of Islam in society. Unfortunately, unbalanced justification by the media tends to cause misconceptions about the Islamic concept, especially in America and Europe. This justification then is often used as a base in constructing the narrative of a game. Moreover, they seem to exploit these justifications in a more apparent manner than other forms of media. In the digital age, video games transform to be one of mainstream media that shapes our comprehension and understanding of the world by constructing, conveying and iterating various representations. Therefore, video game referred as the most potential and effective media to convey positive values to users. "Ibn Battuta" game developed as an interactive media that offer different point of view about Islam, to differentiate it with the other games in general. By exposing Ibn Battuta as one of the Muslim figures who made a glorious milestone in history of science. Ibn Battuta is known as an adventurer, merchant and inspirational figure by spreading the values of Islam to most areas of coastal Asia. The game reveals the travel records of Ibn Battuta in the first half of the 14th century, which also reveals the wide scope of the Muslim life at that time. This paper is based primarily on qualitative research and content analysis. The methodology used for content analysis involves playing the whole Ibn Battuta games while taking notes and screenshots of relevant visual signifiers, recording the narrative and analysing the structure of gameplay. Through Ibn Battuta games, the symbolic and ideological dimensions of in-game representational history related to Islam has been analysed from different perspectives. Immersive worlds as given environments in this game, which may be explored in a nonlinear way by players - include history, artifacts and objects - allow users to learn about the history of Islam by exploring the environment and its objects in a relatively open-ended way. Keywords: Islamic history, interactive game, the structure